Orthokeratology fitting in a Post LASIK Patients : A Case Report: Poster Presentation - Case Report - Ophthalmologist - WENI PUSPITASARI; Ajeng Kartika Ayu Putri (Majalah Oftalmologi Indonesia, 2023)
Introduction : Refractive surgery patients may have residual refractive eror.. Orthokeratology (OK) lenses are a less common option for correcting refractive eror in post refractive surgery patients. This case discusses OK lens as an alternative to LASIK enhancement, patient selection and fitting. Case Illustration : A 34 years old male complaint of blurred vision in both eye . He presented to our clinic with a refraction in the right eye (RE) of S -2.50 cyl -1.25 x 90 and in the the left eye (LE) of S -2.5.00 cyl -1.00 x 80. He underwent bilateral LASIK surgery 10 years ago with recalled refraction of approximately –6.00D in both eyes. Following one week of lens wear, the residual refraction of RE ?1.50 ?0.50 x 90 and LE ?1.50 ?0.50 x 80. After one month,the refraction in RE ?1.00 ?0.50 x 90 and LE ?1.00 ?0.25 x 80. Following a six months, the refraction of RE was -1.00 cyl?0.25 x 90 and-1.00 cyl -0.25x 80 in the LE. He is well satisfied with the level of uncorrected vision throughout the day Discussion : OK lenses are could be an alternative to LASIK enhancement. The good candidate for post refractive surgery in OK, there were no significant corneal irregularity, BCVA 20/20, and K’s reading between 40-46. It is recommended to wait at least 1 year post Lasik before fitting OK lenses and the process may take longer due to oblate cornea. Conclusion : OK lenses are effective alternative to LASIK enhancement. Proper patients selection are vital to achieve a satisfied patient.